Multilayer Electronic Components
By ensuring the internal electrode layer thickness variation exceeds that of the dielectric layer, the laminated electronic component maintains reliability and prevents cracks, enhancing capacitance and performance.
Patent Information
- Application Number
- JP2020195394
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-25
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2040-11-25
AI Technical Summary
When multilayer ceramic capacitors are made thinner, variations in the thickness of the dielectric layer increase, leading to reliability issues and the likelihood of cracks at the interface between the internal electrode layer and the dielectric layer.
The laminated electronic component is designed with a configuration where the variation in the thickness of the internal electrode layer is larger than that of the dielectric layer, ensuring a larger contact area and suppressing crack formation while maintaining reliability.
This design enhances the reliability of the laminated electronic component by preventing cracks and increasing capacitance, with improved accelerated life and higher breakdown voltage.
Smart Images

Figure 0007606330000015 
Figure 0007606330000016 
Figure 0007606330000017
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminated electronic component having a dielectric layer and an internal electrode layer. [Background technology]
[0002] As multilayer ceramic capacitors become thinner, the thickness of the dielectric layers tends to vary more, which can lead to reduced reliability. For example, Patent Document 1 discloses a multilayer ceramic electronic component in which the thickness of the dielectric layers varies (σ) by 100 nm or less in order to improve reliability.
[0003] However, the present inventors have found that suppressing the variation in thickness of the dielectric layers poses a problem in that cracks become more likely to occur at the interfaces between the internal electrode layers and the dielectric layers. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2018-107413 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made in view of the above circumstances, and has an object to provide a multilayer electronic component in which reliability is not deteriorated even when the layers are made thinner, and in which the occurrence of cracks is suppressed. [Means for solving the problem]
[0006] In order to achieve the above object, a laminated electronic component according to the present invention comprises: A laminated electronic component having an element body in which dielectric layers and internal electrode layers are alternately laminated, The variation in thickness of the internal electrode layers is greater than the variation in thickness of the dielectric layers.
[0007] The inventors have found that by having the laminated electronic component configured as described above, the reliability is good and the occurrence of cracks is suppressed even when the laminated electronic component is thinned. The reason for this is believed to be as follows. In the present invention, the contact area between the dielectric layer and the internal electrode layer is large due to the large variation in thickness of the internal electrode layer, so that the occurrence of cracks can be suppressed. In addition, the variation in thickness of the dielectric layer is small, so that the reliability can be made good. Note that good reliability means a long accelerated life and a high breakdown voltage.
[0008] Preferably, the thickness of the dielectric layer and the thickness of the internal electrode layer adjacent to the thickness of the dielectric layer in the stacking direction show a negative correlation.
[0009] Preferably, the standard deviation of the thickness of the internal electrode layers is larger than the standard deviation of the thickness of the dielectric layers.
[0010] Preferably, the variance in thickness of the dielectric layers is statistically significantly smaller than the variance in thickness of the internal electrode layers.
[0011] Preferably, the average thickness of the internal electrode layers is greater than the average thickness of the dielectric layers.
[0012] Preferably, the coverage of the internal electrode layers is 85% or more. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a cross-sectional view of a multilayer ceramic capacitor according to one embodiment of the present invention. [Diagram 2] FIG. 2 is an enlarged cross-sectional view of a portion II in FIG. [Diagram 3] FIG. 3 is a scatter plot for an embodiment of the present invention. [Figure 4] FIG. 4 is an explanatory diagram of a method for manufacturing a multilayer ceramic capacitor according to one embodiment of the present invention. [Diagram 5]FIG. 5 is an explanatory diagram of a method for manufacturing a multilayer ceramic capacitor according to one embodiment of the present invention. [Figure 6] FIG. 6 is an explanatory diagram of a method for manufacturing a multilayer ceramic capacitor according to one embodiment of the present invention. [Figure 7] FIG. 7 is a scatter plot for comparative examples of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] [ First embodiment ] Overall structure of multilayer ceramic capacitor As an embodiment of the laminated electronic component according to the present invention, the overall configuration of a laminated ceramic capacitor will be described.
[0015] 1, a multilayer ceramic capacitor 2 according to this embodiment has an element body 4, a first terminal electrode 6, and a second terminal electrode 8. The element body 4 has dielectric layers 10 and internal electrode layers 12, and the internal electrode layers 12 are alternately laminated between the dielectric layers 10.
[0016] In this embodiment, one of the alternately stacked internal electrode layers 12 is electrically connected to the inside of the first terminal electrode 6 formed on the outside of the first end in the X-axis direction of the element body 4. The other of the alternately stacked internal electrode layers 12 is electrically connected to the inside of the second terminal electrode 8 formed on the outside of the second end in the X-axis direction of the element body 4.
[0017] The shape and size of the multilayer ceramic capacitor 2 may be appropriately determined depending on the purpose and application. When the multilayer ceramic capacitor 2 has a rectangular parallelepiped shape, the dimension in the X-axis direction is preferably 0.4 to 3.2 mm.
[0018] The height dimension (dimension in the Z-axis direction) of the multilayer ceramic capacitor 2 varies depending on factors such as the number of laminated dielectric layers 10 and internal electrode layers 12, but is preferably 0.2 to 2.5 mm. The dimension of the multilayer ceramic capacitor 2 in the Y-axis direction is preferably 0.2 to 2.5 mm.
[0019] The number of laminated dielectric layers 10 is not particularly limited, but is preferably 20 or more, and more preferably 50 or more.
[0020] The material of the dielectric layer 10 is not particularly limited, and may be, for example, ABO 3 It is composed of dielectric materials with a perovskite structure such as ABO 3 In the formula, A is, for example, at least one selected from Ca, Ba, and Sr, and B is at least one selected from Ti and Zr. The molar ratio of A / B is not particularly limited and is 0.980 to 1.020. In addition, a subcomponent such as a Mn compound, a Mg compound, a Cr compound, a Co compound, a Ni compound, a rare earth element, a Si compound, a Li compound, or a B compound may be added to these main components.
[0021] The conductive material contained in the internal electrode layer 12 is not particularly limited. Examples of precious metals used as conductive materials include Pd, Pt, and Ag-Pd alloys. Examples of base metals used as conductive materials include Ni, Ni-based alloys, Cu, and Cu-based alloys. Note that Ni, Ni-based alloys, Cu, and Cu-based alloys may contain various trace components such as P and / or S at about 0.1 mass % or less. The internal electrode layer 12 may be formed using a commercially available electrode paste.
[0022] There is no particular limitation on the conductive material contained in the first terminal electrode 6 and the second terminal electrode 8. For example, known conductive materials such as Ni, Cu, Sn, Ag, Pd, Pt, Au, or alloys of these, conductive resins, etc. may be used. The thicknesses of the first terminal electrode 6 and the second terminal electrode 8 may be appropriately determined depending on the application, etc.
[0023] Fig. 2 is an enlarged cross-sectional view of part II in Fig. 1. In this embodiment, as shown in Fig. 2, both the dielectric layers 10 and the internal electrode layers 12 have thickness variations.
[0024] In this embodiment, the variation in thickness of the internal electrode layers 12 is greater than the variation in thickness of the dielectric layers 10 .
[0025] Specifically, it is preferable that the standard deviation of the thickness of the internal electrode layers 12 is larger than the standard deviation of the thickness of the dielectric layers 10. When the standard deviation of the thickness of the dielectric layers 10 (dielectric σ) relative to the standard deviation of the thickness of the internal electrode layers 12 (electrode σ) is expressed as "dielectric σ / electrode σ", "dielectric σ / electrode σ" is preferably 0.4 or more and 1.0 or less, and more preferably 0.4 or more and 0.8 or less.
[0026] In this embodiment, it is preferable to obtain the standard deviation of the thickness of the dielectric layer 10 by measuring the thickness of the dielectric layer 10 at 100 or more points. Also, in this embodiment, it is preferable to obtain the standard deviation of the thickness of the internal electrode layer 12 by measuring the thickness of the internal electrode layer 12 at 100 or more points.
[0027] In addition, since "standard deviation" is the positive square root of "variance," if the variation is large, the "variance" will be large and the "standard deviation" will also be large. Conversely, if the variation is small, the "variance" will be small and the "standard deviation" will also be small.
[0028] In this embodiment, it is preferable that the variance of the thickness of the dielectric layers 10 is statistically significantly smaller than the variance of the thickness of the internal electrode layers 12. Specifically, it is preferable that the variance of the thickness of the dielectric layers 10 can be determined to be smaller than the variance of the thickness of the internal electrode layers 12 when a one-sided F-test with a significance level of 0.05 is performed.
[0029] In the one-sided F-test, first, a null hypothesis is made that "there is no difference between the variance of the thickness of the dielectric layer 10 and the variance of the thickness of the internal electrode layer 12 (they are equal variances)". Next, an alternative hypothesis is made that "the variance of the thickness of the dielectric layer 10 is smaller than the variance of the thickness of the internal electrode layer 12". Next, a one-sided F-test is performed with a significance level of 0.05 using the measured values of the thickness of the dielectric layer 10 at 100 or more locations and the measured values of the thickness of the internal electrode layer 12 at 100 or more locations to calculate a p-value. If the p-value is smaller than 0.05, the null hypothesis can be rejected. That is, the alternative hypothesis that "the variance of the thickness of the dielectric layer 10 is smaller than the variance of the thickness of the internal electrode layer 12" is adopted. Then, if the alternative hypothesis that "the variance of the thickness of the dielectric layer 10 is smaller than the variance of the thickness of the internal electrode layer 12" is adopted by the one-sided F-test, it can be said that "the variance of the thickness of the dielectric layer 10 is statistically significantly smaller than the variance of the thickness of the internal electrode layer 12".
[0030] In this embodiment, it is preferable that the average thickness ATe of the internal electrode layers 12 is greater than the average thickness ATd of the dielectric layers 10, and it is more preferable that the ratio (ATe / ATd) of the average thickness ATe of the internal electrode layers 12 to the average thickness ATd of the dielectric layers 10 is 1.02 or greater and 1.16 or less.
[0031] In this embodiment, the average thickness ATd of the dielectric layer 10 is preferably 0.6 μm or less. The lower limit of the average thickness ATd of the dielectric layer 10 is not particularly limited, but is, for example, 0.3 μm. In this embodiment, since it is preferable that the variation in thickness of the internal electrode layer 12 is greater than the variation in thickness of the dielectric layer 10, even if the dielectric layer 10 is made thinner, it is possible to suppress the occurrence of cracks and to increase the electrostatic capacitance.
[0032] In this embodiment, the average thickness ATi of the internal electrode layers 12 is preferably 0.65 μm or less. The lower limit of the average thickness ATi of the internal electrode layers 12 is not particularly limited, but is, for example, 0.4 μm.
[0033] In this embodiment, it is preferable that the thickness of the dielectric layer 10 and the thickness of the internal electrode layer 12 adjacent to the thickness of the dielectric layer 10 in the stacking direction (Z-axis direction) have a negative correlation. This point will be explained with reference to FIG.
[0034] 2, after obtaining a cross section parallel to the stacking direction (Z-axis direction) of the multilayer ceramic capacitor 2, multiple imaginary lines L parallel to the stacking direction (Z-axis direction) are drawn. The distance d between adjacent imaginary lines L is preferably 0.5 μm or more and 1 μm or less. In addition, the distance d between adjacent imaginary lines L is preferably greater than the grain size of the dielectric particles.
[0035] Next, the thickness Tda of the dielectric layer 10 on the imaginary line L is measured, and the thickness Tea of the internal electrode layer 12 on the same imaginary line at a location adjacent in the stacking direction (Z-axis direction) to the thickness Tda of the dielectric layer 10 is measured. "The thickness Tea of the internal electrode layer 12 on the same imaginary line L at a location adjacent in the stacking direction (Z-axis direction) to the thickness Tda of the dielectric layer 10" is, in other words, "the thickness Tea of the internal electrode layer 12 adjacent in the stacking direction (Z-axis direction) to the thickness Tda of the dielectric layer 10."
[0036] Similarly, the thickness Tdb of another dielectric layer 10 on another virtual line L is measured, and the thickness Teb of the internal electrode layer 12 on the same virtual line at a location adjacent to the thickness Tdb of the dielectric layer 10 in the stacking direction (Z-axis direction) is measured. Similar operations are performed at 100 or more locations. That is, the "thickness of the dielectric layer 10" is measured at 100 or more locations, and the "thickness of the internal electrode layer 12" is similarly measured at 100 or more locations.
[0037] In this embodiment, there is a negative correlation between the thickness of the dielectric layer 10 and the internal electrode layer 12 adjacent to the dielectric layer 10 in the stacking direction. "There is a negative correlation between the thickness of the dielectric layer 10 and the internal electrode layer 12 adjacent to the dielectric layer 10 in the stacking direction" can be explained as follows, for example, with reference to Figure 3.
[0038] 3, the horizontal axis represents the thickness of the dielectric layer 10, and the vertical axis represents the thickness of the internal electrode layer 12 that contacts the dielectric layer 10 below in the stacking direction (Z-axis direction). In this embodiment, the scatter diagram obtained in this manner shows a negative correlation.
[0039] Although there is no particular limitation on the method for confirming that the scatter plot shows a negative correlation, it is preferable to perform a one-sided test of Pearson's product-moment correlation coefficient with a significance level of 0.05, and determine that there is a negative correlation when the p-value is less than 0.05, for example. When the significance level is 0.05 and the p-value is less than 0.05, the null hypothesis that "the Pearson's product-moment correlation coefficient is 0" is rejected, and the alternative hypothesis that "the Pearson's product-moment correlation coefficient is negative" is adopted, so that it can be determined that the scatter plot shows a negative correlation.
[0040] In this embodiment, the coverage of the internal electrode layer 12 is preferably 85% or more, and more preferably 95% or more. The internal electrode layer 12 shown in Fig. 1 and Fig. 2 is illustrated as being continuous in the Y-axis direction, but in reality, discontinuities in the internal electrode layer 12 are observed in the cross section. The discontinuities in the internal electrode layer 12 in the cross section do not pose any functional problems for the internal electrode layer 12, since the internal electrode layer 12 is continuous in other cross sections. The coverage of the internal electrode layer 12 is calculated as a value (expressed in %) obtained by dividing the total length of the electrodes excluding the discontinuous parts in the cross section of the internal electrode layer 12 by the ideally continuous electrode length.
[0041] Manufacturing method of multilayer ceramic capacitor Next, a method for manufacturing the multilayer ceramic capacitor 2 according to one embodiment of the present invention will be described.
[0042] First, a paste for dielectric layer is prepared in order to manufacture a green sheet that will constitute the dielectric layer 10 shown in FIG. 1 after firing.
[0043] The dielectric layer paste is usually made of an organic solvent-based paste obtained by kneading ceramic powder with an organic vehicle, or a water-based paste.
[0044] The raw material of the ceramic powder can be appropriately selected from various compounds that become the composite oxides or oxides that will form the dielectric layer 10 described above, such as carbonates, nitrates, hydroxides, and organometallic compounds, and can be used by mixing them. In this embodiment, the raw material of the ceramic powder is used as a powder having an average particle size preferably of about 0.01 to 1 μm. In order to make the green sheet extremely thin, it is desirable to use a powder that is finer than the thickness of the green sheet.
[0045] The organic vehicle is a binder dissolved in an organic solvent. The binder used in the organic vehicle is not particularly limited, and may be appropriately selected from various common binders such as butyral, acrylic, ethyl cellulose, etc.
[0046] The organic solvent used is not particularly limited, and may be appropriately selected from various organic solvents such as terpineol, butyl carbitol, alcohol, methyl ethyl ketone, acetone, and toluene depending on the method to be used, such as a printing method or a sheet method.
[0047] The dielectric layer paste may contain additives selected from various dispersants, plasticizers, dielectrics, subcomponent compounds, glass frits, and the like, as necessary.
[0048] Examples of the plasticizer include phthalates such as dioctyl phthalate and benzyl butyl phthalate, adipic acid, phosphates, and glycols.
[0049] Next, an internal electrode layer paste for forming the internal electrode layer 12 shown in FIG. 1 is prepared. The internal electrode layer paste is prepared by kneading the conductive material made of the various conductive metals or alloys described above with the organic vehicle described above. Instead of the conductive material, oxides, organometallic compounds, resinates, etc. can also be used. The oxides, organometallic compounds, and resinates described above become the conductive materials after firing. The internal electrode layer paste may contain ceramic powder (e.g., barium titanate powder) as a co-material, if necessary. The co-material has the effect of suppressing sintering of the conductive powder during the firing process.
[0050] The dielectric layer paste and internal electrode layer paste prepared above are used to form a green sheet 100a that will become the dielectric layer 10 after firing, as shown in Fig. 4. The method for forming the green sheet 100a is not particularly limited, and for example, a printing method or a sheet method can be used. In this embodiment and the embodiments described below, even when the printing method is used, the term "green sheet" is used for the dielectric layer 10 before firing.
[0051] In this embodiment, the green sheet 100a is formed on a support 140 such as a PET film, and then dried.
[0052] Next, an internal electrode pattern layer 120a that will become the internal electrode layer 12 after firing is formed on the green sheet 100a. The method for forming the internal electrode pattern layer 120a is not particularly limited, and for example, a printing method, a transfer method, a sheet method, or the like can be used.
[0053] After the internal electrode pattern layer 120a is formed on the green sheet 100a, it is dried at an atmospheric temperature of Ta° C. to prepare a first sheet body 160a. Ta° C. is preferably 70° C. or more and 100° C. or less, and more preferably 70° C. or more and 80° C. or less.
[0054] Next, as shown in FIG. 5, a green sheet 100b is formed on a support 140 and dried.
[0055] Next, after forming the internal electrode pattern layer 120b on the green sheet 100b, the internal electrode pattern layer 120b is dried at an atmospheric temperature of Tb°C, which is lower than Ta°C.
[0056] (Ta-Tb)°C is preferably 5°C or more and 30°C or less, and more preferably 5°C or more and 25°C or less.
[0057] A green laminate is obtained by alternately laminating a plurality of first sheet bodies 160a and second sheet bodies 160b.
[0058] In this embodiment, the green sheet 100 of the first sheet body 160a A The Young's modulus of the green sheet 100 of the second sheet body 160b b It is preferable to set it higher than the Young's modulus. In addition, it is preferable that the Young's modulus of the internal electrode pattern layer 120a of the first sheet body 160a is higher than the Young's modulus of the internal electrode pattern layer 120b of the second sheet body 160b.
[0059] Specifically, the drying temperature (Ta ° C.) of the green sheet 100a and the internal electrode pattern layer 120a of the first sheet body 160a is set higher than the drying temperature (Tb ° C.) of the green sheet 100b and the internal electrode pattern layer 120b of the second sheet body 160b, thereby A The Young's modulus of the green sheet 100 of the second sheet body 160b b It can be made higher than the Young's modulus. Furthermore, the Young's modulus of the internal electrode pattern layer 120a of the first sheet body 160a can be made higher than the Young's modulus of the internal electrode pattern layer 120b of the second sheet body 160b.
[0060] In this embodiment, it is preferable that the relationship in magnitude of Young's modulus after drying of the green sheet 100a, the internal electrode pattern layer 120a of the first sheet body 160a, the green sheet 100b, and the internal electrode pattern layer 120b of the second sheet body 160b is as follows. Green Sheet 100b <Green sheet 100a <Internal electrode pattern layer 120b <Internal electrode pattern layer 120a
[0061] The obtained green laminate is cut to a predetermined size, for example, along a cutting line, to obtain a green chip. The green chip is solidified by solidification and drying to remove the plasticizer. The green chip after solidification and drying is placed in a barrel container together with media and polishing liquid, and is barrel polished by a horizontal centrifugal barrel machine or the like. The green chip after barrel polishing is washed with water and dried.
[0062] The dried green chip is subjected to a binder removal step, a firing step, and an annealing step as required, to obtain the element body 4 shown in FIG.
[0063] The binder removal conditions are a temperature rise rate of preferably 5 to 300° C. / hour, a holding temperature of preferably 180 to 400° C., and a temperature holding time of preferably 0.5 to 24 hours. The binder removal atmosphere is air or a reducing atmosphere.
[0064] In firing the green chip, the temperature rise rate is preferably 10 to 800° C. / hour, and more preferably 30 to 500° C. / hour.
[0065] The holding temperature during firing is preferably 1150 to 1350° C., more preferably 1200 to 1300° C., and the holding time is preferably 0.5 to 8 hours, more preferably 2 to 3 hours.
[0066] The firing atmosphere is preferably a reducing atmosphere, and the atmospheric gas is, for example, N 2 and H 2 A mixed gas of these can be used after humidification.
[0067] In addition, the oxygen partial pressure during firing may be appropriately determined depending on the type of conductive material in the internal electrode layer paste. When a base metal such as Ni or a Ni alloy is used as the conductive material, the oxygen partial pressure in the firing atmosphere is set to 10 -14 ~10 -10 It is preferable that the pressure is set to MPa.
[0068] After firing in a reducing atmosphere, it is preferable to anneal the element body 4. The annealing is a treatment for reoxidizing the dielectric layer 10, which can significantly extend the IR life (high temperature load life), thereby improving reliability.
[0069] The oxygen partial pressure in the annealing atmosphere is 10 -9 ~10 -5 It is preferable to set the oxygen partial pressure to 10 -9 By setting the pressure to be equal to or higher than MPa, the re-oxidation of the dielectric layer 10 can be carried out efficiently.
[0070] The holding temperature during annealing is preferably 950 to 1150° C. By holding the temperature at 950° C. or higher, the dielectric layer 10 can be easily oxidized sufficiently, and the IR (insulation resistance) and IR life can be easily improved.
[0071] Other annealing conditions include a temperature retention time of preferably 0 to 20 hours and a temperature drop rate of preferably 50 to 500° C. / hour. The annealing atmosphere gas is, for example, humidified N 2 It is preferable to use a gas or the like.
[0072] In the above-mentioned binder removal treatment, firing and annealing, N 2 To humidify gas or mixed gas, for example, a wetter may be used. In this case, the water temperature is preferably about 5 to 75°C.
[0073] The debinding, firing and annealing may be carried out in succession or independently.
[0074] The end faces of the sintered body (element body 4) thus obtained are polished by barrel polishing or the like, and a terminal electrode paste is baked to form the first terminal electrode 6 and the second terminal electrode 8. Then, as necessary, a pad layer is formed by plating the first terminal electrode 6 and the second terminal electrode 8. The terminal electrode paste may be prepared in the same manner as the above-mentioned internal electrode layer paste.
[0075] The multilayer ceramic capacitor 2 thus manufactured is mounted on a printed circuit board by soldering or the like, and is used in various electronic devices.
[0076] In this embodiment, even if the multilayer ceramic capacitor 2 is thinned, the reliability is good, the occurrence of cracks is suppressed, and the capacitance can be increased. The reason for this is believed to be as follows. In the present invention, the variation in thickness of the internal electrode layers 12 is greater than the variation in thickness of the dielectric layers 10, so the contact area between the dielectric layers 10 and the internal electrode layers 12 is large. Therefore, the occurrence of cracks can be suppressed and the capacitance can be increased. In addition, the variation in thickness of the dielectric layers 10 is small, so the reliability can be improved.
[0077] Furthermore, in this embodiment, since the coverage of the internal electrode layers 12 is relatively high, the contact area between the dielectric layers 10 and the internal electrode layers 12 is large, which makes it possible to prevent the occurrence of cracks and to increase the capacitance.
[0078] In this embodiment, it is preferable that the Young's modulus of the green sheet 100a and the internal electrode pattern layer 120a of the first sheet body 160a is higher than the Young's modulus of the green sheet 100b and the internal electrode pattern layer 120b of the second sheet body 160b.
[0079] Due to such a relationship of Young's modulus, the internal electrode pattern layer 120a constituting the first sheet body 160a is relatively hard, so that the internal electrode pattern layer 120a is likely to have a variation in thickness. In addition, the green sheet 100b and the internal electrode pattern layer 120b constituting the second sheet body 160b are relatively soft, so that they are shaped to absorb the variation in thickness of the internal electrode pattern layer 120a constituting the first sheet body 160a. As a result, a predetermined variation in thickness is formed in both the dielectric layer 10 and the internal electrode layer 12 after firing.
[0080] The first sheet body 160a may be rolled after drying. The internal electrode pattern layer 120a constituting the first sheet body 160a has a thickness variation. Since the green sheet 100a has a lower Young's modulus than the internal electrode pattern layer 120a, the rolling causes the thickness variation formed in the internal electrode pattern layer 120a to be reflected in the green sheet 100a. As a result, a predetermined thickness variation is formed not only in the green sheet 100b of the second sheet body 160b but also in the green sheet 100a of the first sheet body 160a.
[0081] [ Second embodiment ] This embodiment is the same as the first embodiment except for the following points. In this embodiment, the Young's modulus of the internal electrode pattern layer is changed by changing the viscosity of the binder constituting the internal electrode pattern layer. As a result, in this embodiment, a predetermined thickness variation is formed in both the dielectric layer 10 and the internal electrode layer 12 after firing.
[0082] In this embodiment, as shown in Fig. 6, a green sheet 100c is formed on a support 140 and dried. Then, an internal electrode pattern layer 120c is formed on the green sheet 100c and dried. Then, a green sheet 100d is formed on the internal electrode pattern layer 120c and dried.
[0083] Next, an internal electrode layer paste is prepared using a binder with a lower viscosity than the binder contained in the internal electrode pattern layer 100c, and the internal electrode pattern layer 120d is formed on the green sheet 100d with this paste, which is then dried to obtain a sheet body 160c.
[0084] The drying temperatures of the green sheet 100c, the internal electrode pattern layer 120c, the green sheet 100d and the internal electrode pattern layer 120d may all be the same or different, but it is preferable that the drying temperature of the green sheet 100d and the internal electrode pattern layer 120d is lower than the drying temperature of the green sheet 100c and the internal electrode pattern layer 120c.
[0085] For example, when ethyl cellulose is used as the binder, the molecular weight of the ethyl cellulose contained in the internal electrode pattern layer 100c is set to 120,000 to 170,000, and the molecular weight of the ethyl cellulose contained in the internal electrode pattern layer 100d is set to 70,000 to 120,000, so that the viscosity of the binder contained in the internal electrode pattern layer 100d can be made lower than the viscosity of the binder contained in the internal electrode pattern layer 100c.
[0086] In this embodiment, a green laminate is obtained by laminating a plurality of sheet bodies 160c.
[0087] In this embodiment, by making the viscosity of the binder of the internal electrode pattern layer 120c higher than that of the binder of the internal electrode pattern layer 120d, the Young's modulus of the internal electrode pattern layer 120c can be made higher than that of the internal electrode pattern layer 120d.
[0088] In this embodiment, it is preferable that the magnitude relationship of the Young's modulus be as follows. Green Sheet 100c ≒Green sheet 100d <Internal electrode pattern layer 120d <Internal electrode pattern layer 120c
[0089] Due to such a relationship of Young's modulus, the internal electrode pattern layer 120c is relatively hard, so that the internal electrode pattern layer 120c is likely to have a variation in thickness. In addition, the green sheet 100d and the internal electrode pattern layer 120d are relatively soft, so that they are shaped to absorb the variation in thickness of the internal electrode pattern layer 120c. As a result, a predetermined variation in thickness is formed in both the dielectric layer 10 and the internal electrode layer 12 after firing.
[0090] In this embodiment, since the green sheet 100c, the internal electrode pattern layer 120c, the green sheet 100d, and the internal electrode pattern layer 120d are coated in layers, it is preferable that the binder used in the dielectric layer paste is an acrylic resin. This makes it difficult for the resin in the lower layer of the green sheet formed by the dielectric layer paste to be damaged.
[0091] [ Third embodiment ] This embodiment is similar to the first embodiment except for the following points: In this embodiment, the internal electrode pattern layer is rolled to form a predetermined thickness variation in both the dielectric layer 10 and the internal electrode layer 12.
[0092] As shown in Fig. 4, a green sheet 100a is formed on a support 140 and dried. Next, an internal electrode pattern layer 120a is formed on the green sheet 100a and dried to prepare a first sheet body 160a. Next, the first sheet body is rolled, and a plurality of rolled first sheet bodies 160a are laminated to obtain a green laminate.
[0093] The drying temperatures for the green sheet 100a and the internal electrode pattern layer 120a may be the same or different.
[0094] In this embodiment, it is preferable that the magnitude relationship of the Young's modulus be as follows. Green Sheet 100a <Internal electrode pattern layer 120a
[0095] Due to such a relationship of Young's modulus, the internal electrode pattern layer 120a is relatively hard, so that the internal electrode pattern layer 120a is likely to have a variation in thickness. In addition, the green sheet 100a is relatively soft, so that the rolling process absorbs the variation in thickness of the internal electrode pattern layer 120a. As a result, a predetermined variation in thickness is formed in both the dielectric layer 10 and the internal electrode layer 12 after firing.
[0096] [ Fourth embodiment ] This embodiment is similar to the first embodiment except for the following points: In this embodiment, the internal electrode pattern layer contains carbon, so that a predetermined thickness variation is formed in both the dielectric layer 10 and the internal electrode layer 12.
[0097] In this embodiment, as shown in FIG. 4, a green sheet 100a is formed on a support 140 and then dried.
[0098] In this embodiment, a paste for internal electrode layers to which carbon is added is used as the paste for internal electrode layers. The amount of carbon added to the paste for internal electrode layers is preferably 0.1 to 2 mass %, more preferably 0.3 to 1 mass %, of the total amount of the paste for internal electrode layers.
[0099] Next, an internal electrode pattern layer 120a to which carbon is added is formed on the green sheet 100a and dried to prepare a first sheet body 160a.
[0100] The drying temperatures for the green sheet 100a and the internal electrode pattern layer 120a may be the same or different.
[0101] A plurality of first sheets 160a are laminated to obtain a green laminate.
[0102] In addition, the temperature rise rate in the firing process of this embodiment is preferably 10 to 800° C. / hour. By making the temperature rise rate in the firing process relatively slow, a low melting point Ba-Ti-Ni alloy is easily formed at the interface between the internal electrode layer 12 and the dielectric layer 10, and the variation of the internal electrode layer 12 can be increased.
[0103] In this embodiment, the presence of carbon contained in the internal electrode pattern layer 120a makes it easier for a low melting point Ba-Ti-Ni alloy to form at the interface between the internal electrode layer 12 and the dielectric layer 10, causing thickness variation in the internal electrode layer 12. As a result, a predetermined thickness variation is formed in the internal electrode layer 12 after firing.
[0104] [ Fifth embodiment ] This embodiment is the same as the second embodiment except for the following points. In this embodiment, the Young's modulus is changed by changing the viscosity of the internal electrode layer paste. As a result, a predetermined thickness variation is formed in both the dielectric layer 10 and the internal electrode layer 12 after firing.
[0105] In this embodiment, as shown in Fig. 6, a green sheet 100c is formed on a support 140 and dried. Then, an internal electrode pattern layer 120c is formed on the green sheet 100c and dried. Then, a green sheet 100d is formed on the internal electrode pattern layer 120c and dried.
[0106] Next, an internal electrode layer paste having a lower viscosity than the internal electrode layer paste used to form the internal electrode pattern layer 100c is used to prepare an internal electrode layer paste, which is used to form an internal electrode pattern layer 120d on the green sheet 100d, and then dried to obtain a sheet body 160c.
[0107] The drying temperatures of the green sheet 100c, the internal electrode pattern layer 120c, the green sheet 100d and the internal electrode pattern layer 120d may all be the same or different, but it is preferable that the drying temperature of the green sheet 100d and the internal electrode pattern layer 120d is lower than the drying temperature of the green sheet 100c and the internal electrode pattern layer 120c.
[0108] Methods for adjusting the viscosity of the internal electrode layer paste include adjusting the contents of the solvent and binder, and adjusting the viscosity of the binder by changing the type or degree of polymerization (molecular weight).
[0109] In this embodiment, the viscosity of the dielectric layer paste used for green sheets 100c and 100d is preferably 20 to 100 cP at a rotation speed of 100 rpm.
[0110] The viscosity of the internal electrode layer paste used for the internal electrode pattern layer 120c and the internal electrode pattern layer 120d is 3×10 3 ~2×10 4 It is preferably cP.
[0111] In this embodiment, a green laminate is obtained by laminating a plurality of sheet bodies 160c.
[0112] In this embodiment, the viscosity of the internal electrode layer paste constituting the internal electrode pattern layer 120c is higher than the viscosity of the internal electrode layer paste constituting the internal electrode pattern layer 120d.
[0113] In this embodiment, it is preferable that the viscosity magnitude relationship be as follows: Dielectric layer paste constituting green sheet 100c ≒ Dielectric layer paste that constitutes green sheet 100d <Internal electrode layer paste constituting the internal electrode pattern layer 120d <Internal electrode layer paste constituting the internal electrode pattern layer 120c
[0114] Due to such a viscosity relationship, the internal electrode pattern layer 120c is relatively hard, so that the internal electrode pattern layer 120c is likely to have a variation in thickness. In addition, the green sheet 100d and the internal electrode pattern layer 120d are relatively soft, so that they are shaped to absorb the variation in thickness of the internal electrode pattern layer 120c. As a result, a predetermined variation in thickness is formed in both the dielectric layer 10 and the internal electrode layer 12 after firing.
[0115] [ Sixth embodiment ] This embodiment is the same as the first embodiment except for the following points: In this embodiment, a conductive material having a variation in particle size distribution is used as the conductive material contained in the internal electrode pattern layer, so that a predetermined thickness variation is formed in both the dielectric layer 10 and the internal electrode layer 12 after firing.
[0116] In this embodiment, a conductive material having a particle size distribution variation is used as the conductive material contained in the internal electrode layer paste. Specifically, a conductive material having a particle size distribution (D90-D10) of preferably 0.01 μm or more and 1 μm or less, more preferably 0.05 μm or more and 0.5 μm or less is used.
[0117] In this embodiment, the particle size distribution of the conductive material contained in the internal electrode pattern layer 120a varies, in other words, the particle size distribution of the conductive material contained in the internal electrode pattern layer 120a is wide. Therefore, the thickness of the internal electrode pattern layer 120a and the internal electrode pattern layer 120b can vary. In addition, since the green sheets 100a and 100b have a lower Young's modulus than the internal electrode pattern layer 120a and the internal electrode pattern layer 120b, the green sheets 100a and 100b also vary in thickness due to the influence of the thickness variation caused in the internal electrode pattern layer 120a and the internal electrode pattern layer 120b. In particular, when the first sheet body and the second sheet body are rolled, respectively, the thickness variation of the green sheets 100a and 100b is more noticeable. As a result, a predetermined thickness variation is formed in both the dielectric layer 10 and the internal electrode layer 12 after firing.
[0118] The present invention is not limited to the above-described embodiment, and various modifications can be made within the scope of the present invention.
[0119] For example, the multilayer electronic component of the present invention is not limited to a multilayer ceramic capacitor, and can be applied to other multilayer electronic components. Examples of other multilayer electronic components include all electronic components in which dielectric layers are laminated via internal electrode layers, such as bandpass filters, multilayer three-terminal filters, piezoelectric elements, PTC thermistors, NTC thermistors, and varistors.
[0120] In addition, in the above embodiment, the Young's modulus is increased by increasing the drying temperature and decreased by decreasing the drying temperature, but the Young's modulus may be increased by increasing the drying time and decreased by shortening the drying time. EXAMPLES
[0121] The present invention will be described in more detail below by way of examples of the present invention, but the present invention is not limited to these examples.
[0122] < Sample No. 3-5 > The main raw material powder is BaTiO 3 Next, SiO powder was added to 100 mole parts of the main raw material. 2 1.27 parts by mole of powder was weighed out, 0.63 parts by mole of MgO powder was weighed out, and Y 2 O 3 Weigh out 0.51 mol parts of the powder and add MnCO 3 Weigh out 0.16 moles of the powder and add V 2 O 5 The powder was weighed out at 0.05 parts by mole. These powders were wet mixed in a ball mill and dried to obtain a dielectric material.
[0123] Next, 100 parts by mass of the obtained dielectric raw material, 7 parts by mass of butyral resin, 4 parts by mass of dioctyl phthalate (DOP) as a plasticizer, 80 parts by mass of methyl ethyl ketone as a solvent, and 2 parts by mass of high molecular weight polyester acid amide amine salt as a dispersant were mixed in a ball mill to form a paste, thereby obtaining a paste for the dielectric layer.
[0124] Separately from the above, 56 parts by weight of Ni particles, 40 parts by weight of terpineol, 4 parts by weight of ethyl cellulose (molecular weight 140,000), and 1 part by weight of benzotriazole were kneaded using a three-roll mill to form a paste, thereby preparing a paste for internal electrode layers.
[0125] Then, using the dielectric layer paste prepared above, a first layer green sheet 100a was formed on a PET film serving as a support 140 as shown in FIG. 4, and dried.
[0126] Next, the second layer of internal electrode pattern layer 120a, which will become internal electrode layer 12 after firing, was formed on the first layer of green sheet 100a using the internal electrode layer paste prepared above, and dried at a temperature (Ta) listed in Table 1 to prepare a first sheet body 160a.
[0127] Next, using the dielectric layer paste prepared above, a first green sheet 100b was formed on a support 140 as shown in FIG. 5, and then dried.
[0128] Next, the second layer of internal electrode pattern layer 120b, which will become internal electrode layer 12 after firing, was formed on the first layer of green sheet 100b using the internal electrode layer paste prepared above, and dried at a temperature (Tb) listed in Table 1 to prepare a second sheet body 160b.
[0129] A green laminate was obtained by alternately laminating a plurality of first sheet bodies 160a and second sheet bodies 160b.
[0130] The Young's moduli after drying of the first green sheet 100a and the second internal electrode pattern layer 120a of the first sheet body 160a, and the first green sheet 100b and the second internal electrode pattern layer 120b of the second sheet body 160b were as shown in Table 1.
[0131] The obtained green laminate was cut along the cutting lines to a predetermined size to obtain a green chip, which was then solidified and dried, barrel-polished, washed with water, and dried.
[0132] Next, the obtained green chip was subjected to a binder removal treatment, sintering, and annealing under the following conditions to obtain a sintered body (element body).
[0133] The conditions for the binder removal treatment were a temperature rise rate of 200° C. / hour, a holding temperature of 260° C., a holding time of 8 hours, and an atmosphere of air.
[0134] The firing conditions were a temperature rise rate of 200°C / hour, a holding temperature of 1000°C, and a holding time of 120 minutes. The temperature drop rate was 200°C / hour. The atmospheric gas was humidified N 2 +H 2 Mixed gas with oxygen partial pressure of 10 -9 The pressure was adjusted to be less than MPa.
[0135] The annealing conditions were: heating rate: 200°C / hour, holding temperature: 1000°C, holding time: 10 hours, cooling rate: 200°C / hour, atmospheric gas: humidified N 2 Gas (oxygen partial pressure: 10 -8 MPa or less).
[0136] A wetter was used to humidify the atmospheric gas during firing and annealing.
[0137] Next, the obtained sintered body was subjected to barrel polishing, after which Cu paste was applied as a terminal electrode and baked in a reducing atmosphere to obtain multilayer ceramic capacitor samples according to sample numbers 3 to 5 (hereinafter sometimes simply referred to as "capacitor samples").
[0138] The size of the obtained capacitor sample was 0.6 mm×0.3 mm×0.3 mm, and the number of dielectric layers 10 sandwiched between the internal electrode layers 12 was 240.
[0139] The obtained capacitor sample was cut parallel to the lamination direction. The obtained cross section was photographed with a scanning electron microscope (SEM), and multiple virtual lines L were drawn as shown in Figure 2. The distance d between adjacent virtual lines L was set to 5 μm.
[0140] Next, the thickness Tda of the dielectric layer 10 on the virtual line L was measured, and the thickness Tea of the internal electrode layer 12 was measured at a location adjacent to and below the measurement location of the thickness Tda of the dielectric layer 10 in the stacking direction (Z-axis direction). The same operation was performed at 100 locations.
[0141] Based on the thickness of the dielectric layer 10 and the thickness of the internal electrode layer 12 measured as described above, each item in Table 2 was calculated.2 is electrode σ 2 The items "Statistically significantly smaller than" and "Negative correlation can be statistically confirmed" were calculated using the following method.
[0142] Dielectric σ 2 is electrode σ 2 Statistically significantly smaller than A one-sided F-test was performed based on the thicknesses of the dielectric layers 10 at 100 locations and the thicknesses of the internal electrode layers 12 at 100 locations measured as described above. In the one-sided F-test, a null hypothesis was first established that "there is no difference between the variance of the thicknesses of the dielectric layers 10 and the variance of the thicknesses of the internal electrode layers 12 (they are equal variances)." Next, an alternative hypothesis was established that "the variance of the thicknesses of the dielectric layers 10 is smaller than the variance of the thicknesses of the internal electrode layers 12." Next, a one-sided F-test with a significance level of 0.05 was performed using the measured values of the thicknesses of the dielectric layers 10 at 100 locations or more and the measured values of the thicknesses of the internal electrode layers 12 at 100 locations or more to calculate a p-value. If the p-value is smaller than 0.05, the null hypothesis can be rejected. In other words, the alternative hypothesis that "the variance of the thicknesses of the dielectric layers 10 is smaller than the variance of the thicknesses of the internal electrode layers 12" is adopted. Then, if the alternative hypothesis that "the variance of the thickness of the dielectric layer 10 is smaller than the variance of the thickness of the internal electrode layer 12" is adopted by the one-sided F-test, then "the variance of the thickness of the dielectric layer 10 (dielectric σ 2 ) is the variance of the thickness of the internal electrode layer 12 (electrode σ 2 ) and determined that it was "statistically significantly smaller than the mean mean."
[0143] Negative correlation can be statistically confirmed In order to confirm that the relationship between the thickness of the dielectric layer 10 and the thickness of the internal electrode layer 12 adjacent to the thickness of the dielectric layer 10 in the stacking direction (Z-axis direction) shows a negative correlation, a one-sided test of Pearson's product-moment correlation coefficient with a significance level of 0.05 was performed based on the thicknesses of the dielectric layer 10 at 100 locations and the thicknesses of the internal electrode layer 12 at 100 locations measured as described above, and it was determined that there was a negative correlation when the p-value was less than 0.05. When the significance level is 0.05 and the p-value is less than 0.05, the null hypothesis that "the Pearson's product-moment correlation coefficient is 0" is rejected and the alternative hypothesis that "the Pearson's product-moment correlation coefficient is negative" is adopted, so it can be said that the scatter diagram shows a negative correlation.
[0144] Fig. 3 is a scatter diagram of sample number 3. In the scatter diagram shown in Fig. 3, the horizontal axis represents the thickness of the dielectric layer 10, and the vertical axis represents the thickness of the internal electrode layer 12 adjacent to the dielectric layer 10 below in the stacking direction (Z-axis direction). It was confirmed that, for sample number 3, the relationship between the thickness of the dielectric layer 10 and the thickness of the internal electrode layer 12 adjacent to the dielectric layer 10 in the stacking direction (Z-axis direction) shows a negative correlation not only from the one-sided test of the Pearson product-moment correlation coefficient but also from Fig. 3.
[0145] Young's Modulus In order to measure the Young's modulus of the green sheet, the dielectric layer paste was applied onto a PET film and dried, and then cut to the desired size. The dried dielectric layer paste was peeled off from the PET film to prepare a sample for Young's modulus measurement.
[0146] When the dielectric layer paste was applied in multiple layers, as in samples 11 and 41 to 43 described below, only one layer was applied onto the PET film, and after drying by giving it the same thermal history, it was cut to the desired size and the dried dielectric paste was peeled off from the PET film to prepare a sample for Young's modulus measurement.
[0147] In order to measure the Young's modulus of the internal electrode pattern layer, the internal electrode paste was applied onto a PET film, and then the film was dried by applying the same thermal history as during printing. The film was then cut to the desired size, and the dried internal electrode paste was peeled off from the PET film to prepare a sample for Young's modulus measurement.
[0148] The obtained sample for measuring Young's modulus was stretched, and the Young's modulus was calculated from the strain and stress at that time.
[0149] Furthermore, the accelerated life, breakdown voltage and number of cracks were measured for the obtained capacitor samples by the following methods. The results are shown in Table 2.
[0150] accelerated life The accelerated life was evaluated by measuring the life time of each capacitor sample while holding it in a DC electric field of 5 V / μm at 160° C. In this example, the above evaluation was performed on 20 capacitor samples, and the failure time was defined as the time from the start of application until the insulation resistance dropped by one digit, and the mean failure time calculated by Weibull analysis was defined as the accelerated life.
[0151] Breakdown Voltage A voltage was continuously applied to the capacitor samples at a rate of 10 V / sec using a breakdown voltage tester, and the voltage at which a current of 10 mA flowed was taken as the breakdown voltage. The breakdown voltages of 20 capacitor samples were measured and the average value was calculated, and the average breakdown voltage was divided by the average thickness of the dielectric layer of the capacitor samples to calculate the dielectric breakdown voltage [V / μm].
[0152] Number of cracks The capacitor samples were mounted on an FR4 board (glass epoxy board) with Sn-Ag-Cu solder, and placed in a pressure cooker tank to carry out an accelerated moisture resistance test for 100 hours at 121°C and 95% humidity. 100 pieces of each capacitor sample were tested. The number of defects for each capacitor sample is shown in Table 1 as the "number of cracks."
[0153] < Sample No. 1 > In sample number 1, a green laminate was obtained by laminating a plurality of first sheets without preparing a second sheet.
[0154] For sample number 1, the temperature increase rate in the firing step was changed as shown in Table 1.
[0155] Except for the above, capacitor samples were prepared and evaluated for each item in the same manner as for samples 3 to 5. The results are shown in Tables 1 and 2.
[0156] < Sample No. 2 > In sample number 2, the second sheet body was not prepared, and multiple first sheets were laminated. A green laminate was obtained.
[0157] Other than the above, capacitor samples were prepared and evaluated for each item in the same manner as for sample numbers 3 to 5. The results are shown in Tables 1 and 2. Also, a scatter diagram of sample number 2 is shown in FIG.
[0158] < Sample No. 11 > 100 parts by mass of dielectric raw material obtained in the same manner as in samples 3 to 5, 7 parts by mass of acrylic resin, 4 parts by mass of dioctyl phthalate (DOP) as a plasticizer, 80 parts by mass of methyl ethyl ketone as a solvent, and 2 parts by mass of high molecular weight polyester acid amide amine salt as a dispersant were mixed in a ball mill to form a paste, thereby obtaining a paste for a dielectric layer to be applied overlay.
[0159] Separately from the above, 56 parts by mass of Ni particles, 40 parts by mass of terpineol, 4 parts by mass of ethyl cellulose (molecular weight 140,000), and 1 part by mass of benzotriazole were kneaded using a three-roll mill to form a paste, thereby preparing a paste for the second internal electrode layer.
[0160] In addition to the above, 56 parts by mass of Ni particles, 40 parts by mass of terpineol, 4 parts by mass of ethyl cellulose (molecular weight 100,000), and 1 part by mass of benzotriazole were kneaded using a three-roll mill to form a paste, thereby preparing a paste for the fourth internal electrode layer.
[0161] Using the dielectric layer paste for overcoating prepared above, a first layer green sheet 100c was formed on a PET film, which is a support 140, as shown in Fig. 6, and then dried. Next, using the second layer internal electrode layer paste prepared above, a second layer internal electrode pattern layer 120c was formed on the first layer green sheet 100c, and then dried. Next, using the dielectric layer paste for overcoating prepared above, a third layer green sheet 100d was formed on the second layer internal electrode pattern layer 120c, and then dried.
[0162] Next, the fourth-layer internal electrode pattern layer 120d was formed on the third-layer green sheet 100d using the fourth-layer internal electrode layer paste prepared above, and dried to obtain a sheet body 160c. After that, a plurality of the sheet bodies 160c were laminated to obtain a green laminate body.
[0163] Other than the above, capacitor samples were prepared and evaluated for each item in the same manner as for samples 3 to 5. The results are shown in Tables 3 and 4.
[0164] <Sample No. 21> For sample number 21, a capacitor sample was prepared in the same manner as sample number 2, except that the first sheet body was rolled, and each item was evaluated. The results are shown in Tables 5 and 6.
[0165] <Sample No. 31> In sample number 31, 0.5 mass % of carbon was added to the total amount of the internal electrode layer paste.
[0166] Other than the above, a capacitor sample was prepared in the same manner as sample No. 2, and each item was evaluated. The results are shown in Tables 7 and 8.
[0167] <Sample No. 41~43> In sample numbers 41 to 43, the amount of solvent added and the type of binder were changed to change the viscosity of the dielectric layer paste constituting the first green sheet, the internal electrode layer paste constituting the second internal electrode pattern layer, the dielectric layer paste constituting the third green sheet, and the internal electrode layer paste constituting the fourth internal electrode pattern layer as shown in Table 9. Except for this, capacitor samples were prepared in the same manner as sample number 11, and each item was evaluated. The results are shown in Tables 9 and 10.
[0168] <Sample No. 51> In sample number 51, the internal electrode layer paste contains BaTiO 3 A capacitor sample was prepared in the same manner as sample number 3, except that 5 parts by mass of the powder was added to 100 parts by mass of nickel powder, and each item was evaluated. The results are shown in Tables 11 and 12.
[0169] <Sample No. 61, 62> For sample numbers 61 and 62, capacitor samples were prepared in the same manner as sample number 3, except that the particle size variation (D90-D10) of the conductive material contained in the internal electrode layer paste was changed as shown in Table 13, and each item was evaluated. The results are shown in Tables 13 and 14. For each sample in Table 14, a test was performed on the number of cracks for 1,000 capacitor samples.
[0170] [Table 1]
[0171] [Table 2]
[0172] [Table 3]
[0173] [Table 4]
[0174]
Table 5
[0175]
Table 6
[0176]
Table 7
[0177]
Table 8
[0178]
Table 9
[0179]
Table 10
[0180]
Table 11
[0181]
Table 12
[0182]
Table 13
[0183]
Table 14
[0184] It was confirmed that when the variation in the thickness of the internal electrode layer was greater than the variation in the thickness of the dielectric layer (sample numbers 3 to 5, 11, 21, 31, 43, 51, 61, and 62), the accelerated life was longer than 1.4 hours, the breakdown voltage was higher than 38 V, and the number of cracks in 100 tests was 0. On the other hand, when the variation in the thickness of the internal electrode layer was smaller than the variation in the thickness of the dielectric layer (sample numbers 1, 2, 41, and 42), it was confirmed that the accelerated life was 1.4 hours or less, the breakdown voltage was 38 V or less, or the number of cracks in 100 tests was greater than 0. [Explanation of symbols]
[0185] 2. Multilayer ceramic capacitor 4... Element body 6... 1st terminal electrode 8... 2nd terminal electrode 10... Dielectric layer 12… Internal electrode layer 100a, 100b, 100c, 100d... Green sheet 120a, 120b, 120c, 120d... Internal electrode pattern layer 140...Support 160a... First sheet body 160b... Second sheet body 160c… Seat body
Claims
1. A laminated electronic component having an element body in which dielectric layers and internal electrode layers are alternately laminated, the variation in thickness of the internal electrode layers is greater than the variation in thickness of the dielectric layers, a relationship between a thickness of the dielectric layer and a thickness of the internal electrode layer adjacent to the thickness of the dielectric layer in a lamination direction shows a negative correlation; The internal electrode layers have an average thickness of 0.60 μm or less, Dielectric σ / electrode σ is 0.48 or more and 0.69 or less, the dielectric σ is the standard deviation of the thickness of the dielectric layer, the electrode σ is the standard deviation of the thickness of the internal electrode layer, The dielectric σ of the laminated electronic component is 0.045 or more.
2. 2. The laminated electronic component according to claim 1, wherein the variance in thickness of said dielectric layers is statistically significantly smaller than the variance in thickness of said internal electrode layers.
3. 3. The laminated electronic component according to claim 1, wherein the average thickness of the internal electrode layers is greater than the average thickness of the dielectric layers.
4. 4. The laminated electronic component according to claim 1, wherein the internal electrode layers have a coverage of 85% or more.
Citation Information
Patent Citations
Composite sheet, laminate and manufacturing method for contact-bonded laminate
JP2006210674A
Multilayer ceramic electronic part
JP2018107413A
Multilayer ceramic electronic component
JP2019087568A
Multi-layered ceramic electronic component and manufacturing method thereof
KR1020190116146A
